Microcontroller Based of Hydroponic Monitoring Environmental Condition (Nusantara Science and Technology Proceedings, 2021)
Hydroponic has developed quite rapidly, we can find almost in every area, from village to metropolis. Hydroponic become a trend because easy to re-implement, easy to reuse, and easy to understand. Hydroponic doesn’t need large area, because hydroponic using water as the main growing medium. Vegetables crops such as chilli, kale, lettuce, spinach, and basil are the type of commonly used in hydroponic. Hydroponic planting main focus is the process of providing nutrient solution as the main food source of plant. Nutrient solution in the form of nutrient A consist of calcium, potassium, nitrogen, and iron. In addition to nutrient A, there is one another called nutrient B. Nutrient B consist of potassium, nitrogen, phosphorus, magnesium, sulphur, manganese, Zn, Cu, Mo, and boron that plant need. Nutrient A and B are very to find in market. Nutrient monitoring in hydroponic system is very important, therefore it should be done periodically and need immediate action when found something odd. Some of equipment needed to monitor the are TDS meter, thermometer, and PH meter. This paper purpose microcontroller based which combine of many sensor needed and fusion it to one module with large display to monitor environmental condition of hydroponic system easily. System can display clearly about temperature, TDS, and also PH of water in hydroponic. Buzzer included to give a notification if something odd happened in the system.